A basic element of it business continuity plan: systematic review - Yusrida Muflihah; Apol Pribadi Subriadi (Jurnal Informatika, 2018)
Implementation of IT in the enterprise raises the possibility of various risks arising from threats and disturbances. Companies need to have business continuity planning (BCP), so that the company's business processes can be sustain in normal or critical situations. BCP is a methodology used to create and validate plan to sustain business operations continuously before, during, and after disasters or disturbing events. BCP is an important part of Business Continuity Management (BCM) and is a step that can be taken to reduce the negative impact of business interruptions caused by internal and external. The current condition of the Business Continuity Plan is the lack of understanding of the key elements of the business continuity plan design that leads companies to realize what business continuity plan are or do not know what is needed to make BCP and BCP owned by the company still lack in completeness of the business continuity strategy. Based on the present condition, this research aims to explore the elements of BCP based on business continuity standard that is COBIT 5 Domain: Manage Continuity, ISO 22301: 2012 Business Continuity Management System, ITIL IT Service Continuity Management and related business continuity plan research. The results of the research are BCP has 8 main elements, determining the need of business continuity management, business continuity review, risk analysis, business impact analysis, business continuity strategy, disaster recovery plan, employee training, BCP testing, where the eight elements can be categorized into two are managerial and technical.